APPLICATION OF MILDRONATE IN THE CONDITIONS OF OXIDATIVE STRESS IN RATS AFFECTED BY SODIUM NITRITE ON THE BACKGROUND OF INTOXICATION WITH TOBACCO SMOKE - Lykhatskyi, P.H.; Fira, L.S. (World of Medicine and Biology, 2017)
Currently, one of the most common anthropogenic agents is tobacco smoke, which has a wide range of effects on the morphofunctional state of various organism systems. Tobacco smoke contains many toxic, mutagenic and carcinogenic chemicals, as well as stable and unstable free radicals and active forms of oxygen that are capable of biological oxidative damage. The current ecological situation in Ukraine has caused significant pollution of natural sources of water supply by various chemicals, in particular nitrates. At the same time, the serious problem of agricultural production is the accumulation of nitrates in crop production. All of the above-mentioned toxicants have a negative effect on the human body, activating oxidative processes, which leads to the intensification of free radical reactions and the deepening of endogenous intoxication. The aim of this study was to investigate the effectiveness of the application of mildronate for the correction of activated oxidative processes and endogenous intoxication in the body of rats of different ages under the conditions of their sodium damage by nitrite and tobacco smoke. Experiments were performed on white rats of different ages. Damage with tobacco smoke was modeled in a sealed chamber from burning 6 cigarettes for 6 minutes (30 days). At 24 and 72 hours before the end of the experiment, animals received sodium nitrite at a dose of 45 mg / kg body weight. Mildronate animals were given at a dose of 120 mg / kg. After 30 days from the beginning of lesion of animals with tobacco smoke they were withdrawn from the experiment by euthanasia under thiopental anesthesia. In carrying out the research, the general principles of animal experimentation were used in accordance with the provisions of the European Convention for the Protection of Vertebrate Animals used for experimental and other scientific purposes. It has been established that after the lesion of all age groups of rats with both toxicants in blood neutrophils, the content of active forms of oxygen is increasing. The defeat of sexually immature rats with tobacco smoke has increased the content of ROS in blood neutrophils by 2.6 times. After 24 hours poisoning of toxic smoke from animals with sodium nitrite, the content of ROS increased by 2.9 times. The use of mildronate reduced this figure by 1.3 times. 72 years after the introduction of sodium nitrite in the affected TS in rats, the content of ROS in blood neutrophils increased 3-fold. The introduction of these mildronate rats has led to a 1.6-fold decrease in this indicator. Similar changes are noted for sexually mature rats. The most effective was mildronate when it was used in aged rats. Defeat over 30 days of tobacco smoke has led to a likely increase in the nitrite-ion content of serum and lung in rats of all age groups. In the myocardium, this indicator has undergone probable changes only in immature rats. The introduction of an additional sodium nitrite toxicant 24 hours before the end of the experiment caused a likely increase in the nitrite-ion content in all investigated animal organs of all age groups. Sexually immature and aging animals were more susceptible to toxicants. In all terms, the study of mildronate positively influenced the nitrite-ion content of blood serum of rats of all age groups, bringing it closer to the level of intact control. In lungs of rats, 24 hours of sodium poisoning with nitrite-toxicated ruminal mumps did not detect the effectiveness of mildronate. Positive effect was shown by mildronate on the myocardium of rats after lesions by both toxicants, effectively reducing the content of this indicator in all groups of animals. The development of oxidative stress after the toxicity of animals has led to the accumulation of middle mass molecules in blood serum. In the study of the content of this indicator after the defeat of sodium nitrite on the background of tobacco intoxication, a significant increase in both blood serum fractions in rats of all age groups was noted. The use of sodium nitrite for 72 hours prior to the end of the experiment led to an increase in the content of medium weight molecules in serum of unborn rats by 3.3 times, in the immature ones - by 3.2 times and in the elderly - by 3.1 times. Introduction to the damaged organism of mildronate led to a decrease in the content of medium molecules in the poisonous organism, although it did not cause any possible changes. Reducing the content of secondary endogenous toxins is probably an indirect response to reducing the intensity of activated oxidation processes in an animal’s body. The obtained results confirmed the antihypoxant and antioxidant properties of mildronate and indicated the absence of sorption properties of this agent.